Direct targeting of risk factors significantly increases the detection of liver cirrhosis in primary care: a cross-sectional diagnostic study utilising transient elastography - Harman, David J.; Ryder, Stephen D.; James, Martin W.; Jelpke, Matthew; Ottey, Dominic S.; Wilkes, Emilie A.; Card, Timothy R.; Aithal, Guruprasad P.; Guha, Indra Neil (BMJ Publishing Group Ltd, 2015)
OBJECTIVES: To assess the feasibility of a novel diagnostic algorithm targeting patients with risk factors for chronic liver disease in a community setting.